2020
DOI: 10.31729/jnma.5113
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Valvular and Non-valvular Atrial Fibrillation and the Application of Antithrombotic Treatment in a Tertiary Care Hospital

Abstract: Introduction: Atrial fibrillation is a common atrial tachyarrhythmia with an increased risk of thromboembolism. This study aims to provide information about the application of antithrombotic treatment based on risk stratification schemes for stroke in real-life clinical practices. Methods: This was a descriptive cross-sectional study in 260 patients admitted at the tertiary care hospital with a diagnosis of atrial fibrillation from January 2019 to February 2020 after approval from the Institutional Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
(11 reference statements)
2
4
0
Order By: Relevance
“…12,19 While other studies in Nepal reported non-valvular causes being its dominant cause. 22,25 In our study, RHD and hypertension were respectively the leading valvular and non-valvular etiologies for AF which is in congruence with the findings of the studies done in other parts of the world. 14,15,26,27 Likewise, in our study, among the valvular causes, mitral stenosis was more prevalent among patients with AF as compared to mitral regurgitation which is supported by two other studies done in Nepal.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…12,19 While other studies in Nepal reported non-valvular causes being its dominant cause. 22,25 In our study, RHD and hypertension were respectively the leading valvular and non-valvular etiologies for AF which is in congruence with the findings of the studies done in other parts of the world. 14,15,26,27 Likewise, in our study, among the valvular causes, mitral stenosis was more prevalent among patients with AF as compared to mitral regurgitation which is supported by two other studies done in Nepal.…”
Section: Discussionsupporting
confidence: 91%
“…20,21 Our study showed female dominance among patients with AF which is similar to the findings from other studies done in Nepal. 7,19,22 Likewise, AF among RHD patients is also found to be more common among females as shown by the two studies done among RHD patients in Nepal. 11,20 But, contrary to our findings, various studies from India and some global studies suggest AF is more common among males as compared to females.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…[9][10][11][12] Our study shows male preponderance of 60.75% as compared to other various study done in our country which showed female preponderance as the studies have included both valvular and nonvolvular AF and as in our country as Rheumatic heart disease involving mitral valve is the most common cause of valvular AF and the common in female patients. [13][14][15][16][17] The mean CHA 2 DS 2 -VaSc and HAS-BLED score were 2.44±1.2 and 1.51±1.4 , respectively showing higher risk of stroke in the study population which were which were similar to other various study Kerala AF registry , Multicenter study in Thailand ,report from the euro heart survey on AF. 10,12,18 The type of atrial fibrillation in ours study as in order with 37.99% had permanent AF followed by 25.31% had paroxysmal AF, 16.45 % had persistent AF, Long standing persistent in 11.39% and first episode in 8.86 % similar to the various other study where permanent AF followed by paroxysmal AF and persistent AF accounts for majority of the type of AF.…”
Section: Discussionsupporting
confidence: 86%
“…6 The scenario in Nepal has been depicted by two studies conducted by Dhungana et al assessing the risk profile and the need for oral Nepalese Heart Journal 2023; Vol. 20(2), [13][14][15][16][17] anticoagulants with risk predicting CHADS2 score > 2. 7,8 These two studies showed that among patients with NVAF only 18.9 %and 25.3% of patients were using anticoagulant (warfarin) respectively.…”
Section: Introductionmentioning
confidence: 99%